Pelatihan Pembuatan Proposal Bagi Mahasiswa Dan Pelajar Dalam Mendapatkan Pinjaman Dana Usaha - Sarlota Arrang Ratang; Michael Ugun (UNIVERSITAS CENDERAWASIH, 2020)
Being an entrepreneur today has become a trend that many young people choose. Not a few college graduates choose to build their own business. In fact, pioneering and building businesses since students. But the very basic thing when a student is about to start becoming an entrepreneur is dana's problem. To meet various needs while fulfilling education at the university, many students need a number of loans that can help meet their financial needs Being an entrepreneur today has become a trend that many young people choose. Not a few college graduates choose to build their own business. In fact, pioneering and building businesses since students. But the very basic thing when a student is about to start becoming an entrepreneur is dana's problem. To meet various needs while fulfilling their education at the university, many students need a number of loans for students that can help meet their financial needs. The purpose of the activity is students and students are able to practice how to make proposals that will be submitted to the Banking, Government, or Universities that provide funding assistance for students in the plan to create small businesses. The results of these training activities broadly include the success of the target number of, trainees, the ability to achieve the objectives, the ability of the planned target material, and the ability of participants in understanding the training material. The target of the training participants as previously planned was 30 students and students around the township in relation in one way or another, then the students who participated in this training numbered 27 students. The figures show that this training/ socialization activity can be said that the target participants reached 90% can be said to be successful/successful.